A method for synthesizing lithium iron phosphate nanomaterials at low temperature

The LiFePO4OH precursor was prepared by low-temperature synthesis method and carbon-thermal reduction, which solved the high cost and complex problems of liquid phase synthesis of LFP materials, and achieved efficient and environmentally friendly nano LiFePO4 material production, improving the performance and safety of the battery.

CN119750534APending Publication Date: 2025-04-04云南烨阳新能源材料有限责任公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411971221.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing liquid-phase synthetic lithium iron phosphate (LFP) battery materials have high production costs, complex post-treatment steps, possible defects and environmental pollution problems.

Method used

The LiFePO4OH precursor was prepared by hydrothermal reaction by low temperature synthesis method, and then mixed with the carbon source to undergo carbon thermal reduction to obtain porous carbon-coated nano LiFePO4 material.

Benefits of technology

It reduces production costs and energy consumption, simplifies the synthesis process, improves the electrochemical performance and safety of the materials, reduces the carbon footprint, and is suitable for large-scale production and environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119750534A_ABST
    Figure CN119750534A_ABST
Patent Text Reader

Abstract

The present invention discloses a method for synthesizing lithium iron phosphate nanomaterials at low temperature, comprising the following steps: step 1) preparing a LiFePO4OH precursor; step 2) mixing the LiFePO4OH precursor with a carbon source; and step 3) synthesizing the LiFePO4 nanomaterial. In the absence of adding a surfactant or a catalyst, wet pre-lithiation is performed through a hydrothermal process to obtain a LiFePO4OH precursor with a stable structure; the LiFePO4OH precursor is mixed with glucose through ball milling, and a porous carbon-coated nano-LiFePO4 is obtained through a carbon thermal reduction process; the present invention first synthesizes FePO4·2H2O raw material into LiFePO4OH under hydrothermal low temperature conditions to avoid dehydration of FePO4·2H2O in a high temperature environment; Fe 3+ Salt instead of Fe used in conventional hydrothermal / solvothermal processes 2+ Salt, avoid Fe 2+ The problem of chemical instability eliminates the need to add a carbon source during the lithiation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery material production, and in particular to a method for synthesizing lithium iron phosphate nanomaterials at low temperature. Background Art

[0002] Lithium iron phosphate (LiFePO4, LFP for short), as a cathode material for lithium-ion batteries, has attracted widespread attention due to its high safety, good cycle stability and low cost. With the rapid development of electric vehicles and portable electronic devices, the demand for batteries with high energy density, high safety and long cycle life is growing, which has promoted the research and application of LFP as a cathode material for batteries.

[0003] At present, in the liquid phase synthesis of lithium iron phosphate in industrial production, the liquid phase synthesis may require the use of more chemical reagents and complex equipment, and the production cost is relatively high; the LFP after liquid phase synthesis usually needs to go through multiple steps such as washing, filtering and drying, which increases the complexity of post-processing; defects such as Fe-Li anti-site may be introduced during the liquid phase synthesis process, affecting the electrochemical properties of the material; the solvent used in the liquid phase synthesis process may have an impact on the environment, and the recovery and treatment of waste liquid need to be considered. Therefore, a method for synthesizing lithium iron phosphate nanomaterials at low temperature is provided. Summary of the invention

[0004] In view of the above problems, the object of the present invention is to provide a method for synthesizing lithium iron phosphate nanomaterials at low temperature.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A method for synthesizing lithium iron phosphate nanomaterials at low temperature comprises the following steps:

[0007] Step 1) Preparation of LiFePO4OH precursor:

[0008] The iron source FePO4·2H2O and the lithium source LiOH·H2O are added to deionized water and stirred to form a suspension; the suspension is added to an autoclave and then placed in a preheating furnace for hydrothermal reaction, and after the reaction is completed, the autoclave is cooled to room temperature and then washed with deionized water; the washed precipitate is filtered and dried to obtain a LiFePO4OH precursor;

[0009] Step 2) Mixing LiFePO4OH precursor with carbon source:

[0010] A LiFePO4OH precursor is mixed with a carbon source, and then ventilated and air-dried to obtain a mixture;

[0011] Step 3) Synthesis of LiFePO4 nanomaterials:

[0012] The mixture is heated in a high temperature furnace, cooled to room temperature after the reaction is completed, and then air flow crushed to obtain LiFePO4 nanomaterials.

[0013] Further: in the step 2), after the LiFePO4OH precursor is mixed with the carbon source, the conductive material is first added, and then the dispersant is added.

[0014] Further: the dispersant is ethanol or deionized water.

[0015] Furthermore: in step 2), the conductive material is selected from one of carbon nanotubes, graphene, conductive carbon black, and graphite suspension.

[0016] Furthermore: the mass ratio of the conductive material to the mixture is 1 to 5:100.

[0017] Further: in the step 2), a ball mill is used for mixing, the ball milling speed is 200 to 800 rpm, and the ball milling time is 2 to 12 hours.

[0018] Further: in the step 3), the high temperature furnace is heated in a nitrogen atmosphere or an argon atmosphere.

[0019] Furthermore: in the step 3), the heating rate of the high temperature furnace is 3-10°C / min, the sintering temperature is 550-650°C, and the holding time is 3-10h.

[0020] Compared with the prior art, the present invention has at least one of the following beneficial effects:

[0021] (1) The present invention uses FePO4·2H2O and LiOH·H2O as raw materials, and performs wet pre-lithiation through a hydrothermal process without adding a surfactant or a catalyst to obtain a LiFePO4OH precursor with a stable structure; the LiFePO4OH precursor is mixed with glucose through ball milling, and a porous carbon-coated nano-LiFePO4 is obtained through a carbon thermal reduction process; the present invention first synthesizes the FePO4·2H2O raw material into LiFePO4OH under hydrothermal low-temperature conditions, thereby avoiding the dehydration of FePO4·2H2O under a high-temperature environment; FePO4·2H2O is used to prepare a LiFePO4OH precursor; and LiFePO4·2H2O is used to prepare a LiFePO4OH precursor. 3+ Salt instead of Fe used in conventional hydrothermal / solvothermal processes 2+ Salt, thus avoiding Fe 2+ The problem of chemical instability is eliminated and the need to add a carbon source during the lithiation process is eliminated.

[0022] (2) The present invention uses FePO4·2H2O and LiOH·H2O in a molar ratio of 1:1, and does not require excess lithium. The LFP material obtained by controlling the stoichiometric ratio and reaction conditions has a higher purity, reduces the possibility of impurities and side reactions, and improves the overall performance and safety of the battery.

[0023] (3) The low-temperature crystallization process (550-650°C) adopted in the present invention is much lower than the high temperature of 750°C or above required by the traditional solid-phase synthesis method, which significantly reduces energy consumption and production costs, while reducing the heat-induced defects that may be generated at high temperatures.

[0024] (4) By optimizing the crystallization temperature, the method of the present invention inhibits the further growth of LFP crystals, and the primary particle size is reduced from the general 300-500 nanometers to 50-300 nanometers, shortening the diffusion path of lithium ions, thereby improving the ion diffusion rate and electrochemical activity of the material.

[0025] (5) Compared with the traditional solid-phase and liquid-phase synthesis methods, the wet pre-lithiation and carbon thermal reduction steps adopted in the present invention simplify the synthesis process, facilitate large-scale production, and help reduce manufacturing complexity and cost.

[0026] (6) Due to the high energy efficiency of the low-temperature synthesis process, it helps to reduce the carbon footprint of the battery production process, promotes the sustainable development of the lithium-ion battery manufacturing industry, and is in line with the current pursuit of environmental protection and green chemical processes. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the XRD diagram of Example 1 of the present invention.

[0028] Figure 2 This is the SEM image of Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0030] Example 1

[0031] FePO4·2H2O and LiOH·H2O were added into deionized water in a molar ratio of 1:1, the mass of deionized water was 10 times the mass of FePO4·2H2O, and stirred evenly to form a uniform suspension; the suspension was poured into a stainless steel autoclave with a polytetrafluoroethylene liner, sealed and placed in a preheating furnace, and a hydrothermal reaction was carried out in the preheating furnace at 230°C while stirring for 10 hours; after the reaction was completed, it was naturally cooled to room temperature, taken out and washed with deionized water, filtered and dried to obtain a LiFePO4OH precursor.

[0032] The obtained LiFePO4OH precursor was mixed with glucose in a mass ratio of 10:1, put into a ball mill, carbon nanotubes were added as a conductive agent, the mass ratio of the carbon nanotubes to the mixture was 1:100, and ethanol was used as a dispersant, and the mass of ethanol was 5 times that of the LiFePO4OH precursor; the mixture was ball milled at a speed of 200 rpm on a ball mill for 12 hours. After the ball milling was completed, the mixture was taken out and placed in a fume hood to dry to obtain a mixture.

[0033] The obtained mixture was placed in a crucible of a high-temperature furnace and heated to 550°C at a heating rate of 3°C / min in a nitrogen atmosphere and kept at this temperature for 10 hours;

[0034] The carbon produced by the decomposition of the carbon source in the high temperature furnace helps to reduce Fe 3+ to Fe 2+ , and form a carbon coating on the surface of LiFePO4 to improve the conductivity of the material. The reaction equation is as follows:

[0035] 12LiFePO4OH+C6H 12 O6·H2O→12LiFePO4+6CO↑+13H2O↑

[0036] C6H 12 O6·H2O→6C+7H2O↑

[0037] After the reaction is completed, the mixture is naturally cooled to room temperature and then air flow crushed to finally obtain LiFePO4 nanomaterials.

[0038] Example 2

[0039] FePO4·2H2O and LiOH·H2O were added into deionized water in a molar ratio of 1:1, the mass of deionized water was 10 times the mass of FePO4·2H2O, and stirred evenly to form a uniform suspension; the suspension was poured into a stainless steel autoclave with a polytetrafluoroethylene liner, sealed and placed in a preheating furnace, and a hydrothermal reaction was carried out in the preheating furnace at 230°C while stirring for 10 hours; after the reaction was completed, it was naturally cooled to room temperature, taken out and washed with deionized water, filtered and dried to obtain a LiFePO4OH precursor.

[0040] The obtained LiFePO4OH precursor is mixed with glucose in a mass ratio of 10:1, put into a ball mill, and graphene is added as a conductive agent, the mass ratio of graphene to the mixture is 1:100, and ethanol is added as a dispersant, and the mass of ethanol is 5 times that of the LiFePO4OH precursor; ball milling is carried out on a ball mill at a speed of 200 rpm for 12 hours. After the ball milling is completed, the mixture is taken out and placed in a fume hood to dry to obtain a mixture.

[0041] The obtained mixture was placed in a crucible of a high-temperature furnace, heated to 600°C at a heating rate of 3°C / min in an argon atmosphere, and kept at this temperature for 10 hours;

[0042] The carbon produced by the decomposition of the carbon source in the high temperature furnace helps to reduce Fe 3+ to Fe 2+ , and form a carbon coating on the surface of LiFePO4 to improve the conductivity of the material. The reaction equation is as follows:

[0043] 12LiFePO4OH+C6H 12 O6·H2O→12LiFePO4+6CO↑+13H2O↑

[0044] C6H 12 O6·H2O→6C+7H2O↑

[0045] After the reaction is completed, the mixture is naturally cooled to room temperature and then air flow crushed to finally obtain LiFePO4 nanomaterials.

[0046] Example 3

[0047] FePO4·2H2O and LiOH·H2O were added into deionized water in a molar ratio of 1:1, the mass of deionized water was 10 times the mass of FePO4·2H2O, and stirred evenly to form a uniform suspension; the suspension was poured into a stainless steel autoclave with a polytetrafluoroethylene liner, sealed and placed in a preheated furnace, and a hydrothermal reaction was carried out in the preheated furnace at 210°C while stirring for 16 hours; after the reaction was completed, it was naturally cooled to room temperature, taken out and washed with deionized water, filtered and dried to obtain a LiFePO4OH precursor.

[0048] The obtained LiFePO4OH precursor is mixed with sucrose in a mass ratio of 10:0.8, put into a ball mill, and then conductive carbon black is added as a conductive agent, the mass ratio of the conductive carbon black to the mixture is 1:100, and deionized water is added as a dispersant, and the mass of the deionized water is 5 times that of the LiFePO4OH precursor; ball milling is performed on a ball mill at a speed of 800 rpm for 2 hours. After the ball milling is completed, the mixture is taken out and placed in a fume hood to dry to obtain a mixture.

[0049] The obtained mixture was placed in a crucible of a high-temperature furnace, heated to 650°C at a heating rate of 10°C / min in an argon atmosphere, and kept at this temperature for 3 hours;

[0050] The carbon produced by the decomposition of the carbon source in the high temperature furnace helps to reduce Fe 3+ to Fe 2+ , and form a carbon coating on the surface of LiFePO4 to improve the conductivity of the material. The reaction equation is as follows:

[0051] 12LiFePO4OH+C6H 12 O6·H2O→12LiFePO4+6CO↑+13H2O↑

[0052] C6H 12 O6·H2O→6C+7H2O↑

[0053] After the reaction is completed, the mixture is naturally cooled to room temperature and then air flow crushed to finally obtain LiFePO4 nanomaterials.

[0054] Example 4

[0055] FePO4·2H2O and LiOH·H2O were added into deionized water in a mass ratio of 1:1, the mass of deionized water was 10 times the mass of FePO4·2H2O, and stirred evenly to form a uniform suspension; the suspension was poured into a stainless steel autoclave with a polytetrafluoroethylene liner, sealed and placed in a preheated furnace, and a hydrothermal reaction was carried out in the preheated furnace at 210°C while stirring for 16 hours; after the reaction was completed, it was naturally cooled to room temperature, taken out and washed with deionized water, filtered and dried to obtain a LiFePO4OH precursor.

[0056] The obtained LiFePO4OH precursor is mixed with sucrose in a mass ratio of 10:0.8, put into a ball mill, and then a graphite suspension is added as a conductive agent, the mass ratio of the graphite suspension to the mixture is 3:100, and deionized water is added as a dispersant, and the mass of ethanol is 5 times that of the LiFePO4OH precursor; ball milling is carried out on a ball mill at a speed of 500 rpm for 2 hours. After the ball milling is completed, the mixture is taken out and placed in a fume hood to dry to obtain a mixture.

[0057] The obtained mixture was placed in a crucible of a high-temperature furnace and heated to 650°C at a heating rate of 8°C / min in a nitrogen atmosphere and kept at this temperature for 7 hours;

[0058] The carbon produced by the decomposition of the carbon source in the high temperature furnace helps to reduce Fe 3+ to Fe 2+ , and form a carbon coating on the surface of LiFePO4 to improve the conductivity of the material. The reaction equation is as follows:

[0059] 12LiFePO4OH+C6H 12 O6·H2O→12LiFePO4+6CO↑+13H2O↑

[0060] C6H 12 O6·H2O→6C+7H2O↑

[0061] After the reaction is completed, the mixture is naturally cooled to room temperature and then air flow crushed to finally obtain LiFePO4 nanomaterials.

[0062] Comparative Example

[0063] The FePO4 precursor, Li2CO3 and sucrose were mixed in a mass ratio of 4:1:0.2, put into a ball mill, and deionized water as a dispersant was added, the mass of deionized water was 5 times that of the FePO4 precursor; ball milling was performed at a speed of 600 rpm on a ball mill for 6 hours. After the ball milling was completed, the mixture was taken out and placed in a fume hood to dry to obtain a mixture.

[0064] The obtained mixture was placed in a crucible of a high-temperature furnace, heated to 790°C at a heating rate of 5°C / min in a nitrogen atmosphere, and kept warm for 10 hours; after the reaction was completed, it was naturally cooled to room temperature and then air flow crushed to finally obtain a LiFePO4 control sample.

[0065] Battery assembly and charge and discharge testing

[0066] Using nmp as solvent, the active material, conductive carbon black and polytetrafluoroethylene were uniformly mixed in a mass ratio of 90:5:5, and the obtained slurry was evenly coated on a flat aluminum foil, and then vacuum dried at 120℃ for 10h to make a circular electrode with a diameter of 12mm. In a glove box filled with argon, the positive electrode shell, electrode, diaphragm, lithium sheet, nickel foam and negative electrode shell were assembled into a CR2025 button half-cell in the order of positive electrode shell, electrode, diaphragm, lithium sheet, nickel foam and negative electrode shell, in which the lithium sheet was the counter electrode, the diaphragm was Celgard 2400 polypropylene film, and the electrolyte composition was 1mol / LLiPF6 / (DMC+DEC+EC), in which DMC, DEC and EC were dimethyl carbonate, diethyl carbonate and ethylene carbonate, respectively, and the volume ratio of DMC, DEC and EC was 1:1:1. The charge-discharge and rate performance tests were carried out using a CT2001A battery tester produced by Wuhan Blue Electric Electronic Technology Co., Ltd. The voltage range was 2.00-3.75V and the test temperature was 25°C. The test results are shown in Table 1.

[0067] Table 1 Electrochemical performance comparison

[0068]

[0069] As shown in Table 1, the electrochemical properties of the LFP samples prepared by the method of the present invention are significantly better than those of the comparative examples, and Example 1 has the best performance, with 0.1C, 1C, and 5C discharge capacities of 163.2 mAh / g, 155.9 mAh / g, and 140.5 mAh / g, respectively.

[0070] At the same time, XRD and SEM tests were performed on the sample of Example 1. From the XRD graph, it can be seen that the sample has fewer impurity peaks and a purer crystal phase; from the SEM graph, it can be seen that the primary particle size of the sample is small, basically distributed between 50 and 300 nm, and the size is relatively uniform.

[0071] The physical properties of the various embodiments and comparative examples are shown in Table 2.

[0072] Table 2 Physical properties comparison table

[0073]

[0074] It can be seen from Table 2 that the particle size and resistivity of the LFP sample prepared by the method of the present invention are significantly smaller than those of the comparative example, and the specific surface area is larger than that of the comparative example, which are conducive to the LFP material to exert more capacity under high current charging and discharging (such as 5C) and have better electrochemical performance.

[0075] Although the present invention is described herein with reference to a number of illustrative embodiments of the present invention, it will be appreciated that those skilled in the art may devise many other modifications and implementations that fall within the scope and spirit of the principles disclosed herein. More specifically, within the scope of the present disclosure, drawings, and claims, a variety of variations and modifications may be made to the components and / or layout of the subject combination layout. In addition to the variations and modifications made to the components and / or layout, other uses will also be apparent to those skilled in the art.

Claims

1. A method for synthesizing lithium iron phosphate nanomaterials at low temperature, characterized in that: The following steps are involved: Step 1) Preparation of LiFePO4OH precursor: The iron source FePO4·2H2O and the lithium source LiOH·H2O are added to deionized water and stirred to form a suspension; the suspension is added to an autoclave and then placed in a preheating furnace for hydrothermal reaction, and after the reaction is completed, the autoclave is cooled to room temperature and then washed with deionized water; the washed precipitate is filtered and dried to obtain a LiFePO4OH precursor; Step 2) Mixing LiFePO4OH precursor with carbon source: A LiFePO4OH precursor is mixed with a carbon source, and then ventilated and air-dried to obtain a mixture; Step 3) Synthesis of LiFePO4 nanomaterials: The mixture is heated in a high temperature furnace, cooled to room temperature after the reaction is completed, and then air flow crushed to obtain LiFePO4 nanomaterials.

2. The method for low-temperature synthesis of lithium iron phosphate nanomaterials according to claim 1, characterized in that: In the step 2), after the LiFePO4OH precursor is mixed with the carbon source, a conductive material is first added, and then a dispersant is added.

3. The method for low-temperature synthesis of lithium iron phosphate nanomaterials according to claim 2, characterized in that: The dispersant is ethanol or deionized water.

4. The method for low-temperature synthesis of lithium iron phosphate nanomaterials according to claim 2, characterized in that: In the step 2), the conductive material is selected from one of carbon nanotubes, graphene, conductive carbon black, and graphite suspension.

5. The method for low-temperature synthesis of lithium iron phosphate nanomaterials according to claim 4, characterized in that: The mass ratio of the conductive material to the mixture is 1 to 5:

100.

6. The method for low-temperature synthesis of lithium iron phosphate nanomaterials according to claim 1, characterized in that: In the step 2), a ball mill is used for mixing, the ball milling speed is 200 to 800 rpm, and the ball milling time is 2 to 12 hours.

7. The method for low-temperature synthesis of lithium iron phosphate nanomaterials according to claim 1, characterized in that: In the step 3), the high temperature furnace is heated in a nitrogen atmosphere or an argon atmosphere.

8. The method for low-temperature synthesis of lithium iron phosphate nanomaterials according to claim 1, characterized in that: In the step 3), the heating rate of the high temperature furnace is 3-10° C. / min, the sintering temperature is 550-650° C., and the holding time is 3-10 h.

Citation Information

Cited By

  • High-temperature-resistant low-iron-dissolution lithium iron phosphate material as well as preparation method and application thereof

    CN120664513A